Alternative methodology for traditional interventions: A colonial painting and its lining with the nap bond method - Morales, Ana (2016)
Lining treatments used in the conservation-restoration field can be classified according to the adhesive used. Traditional methods include those based on glue-starch and wax-resin whilst those using synthetic adhesives are considered alternative methods. Rise of new materials and mechanical equipment like the low-pressure table expanded possibilities of intervention. However, alternative methods require previous exhaustive testing of procedures, tools and supplies. This paper describes research carried out by an interdisciplinary team of conservators, historians and chemists from the IIPC-TAREA that elucidated fundamental aspects of a painting of San Luis Gonzaga from the South American colonial period, deteriorated but with an important documentary value. In the case here presented a minimal intervention restoration criterion was applied and the nap bond method used proved to be the most suitable alternative lining for this particular situation.